Typology of conventional and agroecological vegetable production systems in the Campos Gerais region of Paraná, Brazil - Demiate, Michel Mottin; de Sena, José Ozinaldo Alves (Seven Editora, 2024)
In the region of Campos Gerais do Paraná, family farming has a large share in the production of food for direct consumption, such as vegetables. As in the rest of the state and the country, it has been observed that in recent years there has been a distinction between vegetable production systems, especially with the growing stimulus to the consumption of agroecological products. In this context, the objective of this study was to characterize the production systems of conventional and agroecological vegetables, analyzing the typology, in the municipalities of Castro, Palmeira and Ponta Grossa, through multivariate statistical analysis. For this, 29 rural properties were previously selected in the three municipalities mentioned, in which a semi-structured questionnaire was applied. The properties were selected together with technicians from EMATER-PR (regional and local office) and municipal governments, with the basic criteria: having olericulture as their main activity and fitting the profile of family farming. Social, technical-agronomic, economic and financial information was collected. The collected data were tabulated and transformed into numerical values. Subsequently, they were statistically treated using principal component analysis. Of the 29 rural properties interviewed, 19 used the conventional vegetable production system and were mostly located in Ponta Grossa. As for the properties that use the agroecological production system, it can be seen that they were better distributed among the municipalities of Ponta Grossa (4 properties), Palmeira (3 properties) and Castro (3 properties). It was found that the time that the family has lived on the property was not a determining factor for the distinction of the production systems. However, the time they have been in the activity and the area used in the cultivation of vegetables were extremely important variables. It can be observed that the properties in agroecological system are more recent and use a smaller cultivated area. Principal component analysis proved to be a promising tool for this type of study, as it allowed the analysis of technical-agronomic, economic and financial variables, both internal and external to the property, so that it was possible to distinguish differences between conventional and agroecological vegetable production systems. With this, it can be assessed that the complexity between the vegetable production systems in Campos Gerais do Paraná is high. The agroecological system is the one that presents the greatest problems with the control of pests and diseases, even in smaller cultivation areas, which implies lower income for the property, even though producers have a higher frequency of commercialization. For the conventional system, although the cultivation areas are larger, the lack of knowledge of financial management tools, low demand for training and updates are factors that impact the production and sustainability of the property. DOI:https://doi.org/10.56238/sevened2024.023-023